2018
DOI: 10.1007/s00330-018-5309-2
|View full text |Cite
|
Sign up to set email alerts
|

Shear-wave elastography can evaluate annulus fibrosus alteration in adolescent scoliosis

Abstract: • Adolescent idiopathic scoliosis may have an altered lumbar annulus fibrosus. • Shear-wave elastography can quantify lumbar annulus fibrosus mechanical properties. • Shear-wave speed was higher in scoliotic annulus than in healthy subjects. • Elastography showed potential as a biomechanical marker for characterizing disc alteration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…On the other hand, 40% of the patients who presented abnormally high axial vertebral torque also had IAR at junctions within the normality corridor (Table 2). Disc ultrasonographic elastography of normal and scoliotic of intervertebral discs recently suggested that scoliotic discs may be stiffer than normal ones [16]; therefore, IAR could be a secondary factor.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, 40% of the patients who presented abnormally high axial vertebral torque also had IAR at junctions within the normality corridor (Table 2). Disc ultrasonographic elastography of normal and scoliotic of intervertebral discs recently suggested that scoliotic discs may be stiffer than normal ones [16]; therefore, IAR could be a secondary factor.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, increased intervertebral torsion is characteristic of the progressive scoliosis geometric phenotype (Skalli et al 2017), suggesting a role of altered disc torsional behaviour, which in turn can be affected by lamellar structure (Adam et al 2015). Moreover, it is known that scoliotic spines are stiffer than healthy ones (Deviren et al 2002), and recent in vivo measurements showed that this increased stiffness could be due to the AF (Langlais et al 2018). Mechanical and microstructural alterations of the disc have been already demonstrated in adolescent idiopathic scoliosis patients (Yu et al 2005; Langlais et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is known that scoliotic spines are stiffer than healthy ones (Deviren et al 2002), and recent in vivo measurements showed that this increased stiffness could be due to the AF (Langlais et al 2018). Mechanical and microstructural alterations of the disc have been already demonstrated in adolescent idiopathic scoliosis patients (Yu et al 2005; Langlais et al 2018). If these changes are accompanied by morphological ones, the technique tested in this work could be used to assess them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The external compression to the tissue studied by quasistatic elastography made this kind of investigation not suitable for spinal cord lesions. Nonetheless the introduction of related techniques, based on acoustic radiation force impulse imaging and shearwave elasticity imaging, allowed to overcome this limitation and to reconstruct 2-D and 3-D stiffness maps of a given tissue (53). Those new concepts have been recently extended also to the field of neurosurgery; for instance Uff et al demonstrated that elastograms can be successfully generated in the spinal cord using vascular pulsations to generate internal strains: their results revealed a correlation between strain data and the surgeon's assessment of the stiffness of the tissues; furthermore they found that areas of reduction in cross-correlation coefficient and very high axial strain at tumor boundaries predicted cleavage planes (54).…”
Section: Challenges and Future Opportunitiesmentioning
confidence: 99%